A new era of therapy for hepatitis C virus infection. Issue 5 (October 2015) - Nyalakonda, Harita; Utay, Netanya S.
<x xml:space="preserve">Abstract</x> Purpose of review Previous treatments with pegylated interferon (PEG-IFN) and ribavirin for hepatitis C virus (HCV) infection resulted in significant adverse events and low cure rates, even with the addition of first-generation protease inhibitors. The standard of care for chronic HCV infection changed dramatically in 2013 with the approval of second-generation direct-acting antivirals, which led the way for IFN-free combination regimens. Recent findings All-oral combinations of direct-acting antivirals, with or without ribavirin, have shown high efficacy and are well tolerated in patients with the predominant genotypes, advanced fibrosis stages, and HIV co-infection. New fixed-dose co-formulations of direct-acting antivirals have allowed simpler regimens with shorter treatment durations and low rates of discontinuation, but are associated with substantial costs. Summary Since 2013, all-oral, IFN-free regimens with direct-acting antivirals have quickly become the mainstay of treatment for HCV infection as they provide high rates of sustained virologic response with a relatively short duration of treatment and low side-effect profile.